Increase of Meningitis Risk in Stroke Patients in Taiwan - Wang, Chie-Hong; Lin, Tsung-Li; Muo, Chih-Hsin; Lin, Chen-Huan; Huang, Yu-Chuen; Fu, Ru-Huei; Shyu, Woei-Cherng; Liu, Shih-Ping (Frontiers in Neurology, 2018)
Background and purpose: The blood-brain barrier (BBB) not only provides a physical obstruction, but also recruits and activates neutrophils in cases of infection. Hemorrhagic or ischemic stroke reportedly induces the disruption of the BBB. However, few studies have reported a correlation between the incidence of meningitis in patients with a history of stroke. The present study tested the hypothesis that patients with a history of stroke may be more vulnerable to meningitis. Methods: Stroke and age-matched comparison (n = 29,436 and 87,951, respectively) cohorts were recruited from the Taiwan National Health Insurance (TNHI) database (2000 to 2011). Correlations between the two cohorts were evaluated by Cox proportional hazard regression model, Kaplan-Meier curve, and log-rank tests. Results: The incidence of meningitis was higher in the stroke cohort compared to that in the comparison cohort (hazard ratio [HR], 2.89; 95% confidence interval [CI], 2.23-3.74, p < 0.001). After adjusting for age, sex, and comorbidities, the estimated hazard ratio in the stroke cohort was 2.55-fold higher than that in the comparison cohort (CI, 1.94-3.37, p < 0.001). Notably, patients who had experienced hemorrhagic stroke had a higher incidence rate of meningitis than those with a history of ischemic stroke, except for patients older than 75 years of age (incidence rates in hemorrhagic/ischemic stroke patients, 3.14/1.48 in patients younger than 45 years of age, 1.52/0.41 in 45-64-years group, 1.15/0.90 in 65-74-years group, 0.74/0.93 in patients older than 75 years of age). Moreover, stroke patients who had undergone head surgery had the highest meningitis risk (adjusted HR, 8.66; 95% CI, 5.55-13.5, p < 0.001) followed by stroke patients who had not undergone head surgery (adjusted HR, 2.11; 95% CI, 1.57-2.82, p < 0.001). Conclusions: Our results indicated that stroke patients have higher risks of meningitis. Compromised BBB integrity in stroke patients may lead to increased vulnerability to infectious pathogens. In summary, our study provided new evidence of the clinical relationship between stroke and meningitis and our findings suggest the need for precautions to prevent meningitis in stroke patients.